Conidiobolus antarcticus, a new species from continental Antarctica - TOSI, SOLVEIG; CARETTA, GIUSEPPE; Humber R. A. (2004)
Conidiobolus antarcticus sp. nov. (Entomoplithorales: Ancylistaceae), was isolated from the antarctic mosses Scistidium antarctici and Hennediella heimii. It is the first record of an Entomophthorales species in continental Antarctica. This new fungus is distinguished from other species of the same genus in the size and shape of the primary conidia and zygospores, and in the disjunctive mycelial hyphae.